Fast access authentication scheme for mobile IPv6 hierarchical network - Shan-shan SONG; Tao SHANG; Jian-wei LIU (Tongxin xuebao)
A fast access authentication scheme for mobile IPv6 hierarchical network was proposed, which improves the performance of access authentication of mobile IPv6 hierarchical network from two aspects, efficiency and security. Firstly, the scheme used the vector network address coding method to improve the home registration performance. Sec-ondly, a hierarchical lattice-based signature scheme was designed to implement the two-way authentication and improve the security of the authentication process. The analysis of the scheme shows that it is strongly unforgeable, and mean-while it can defend replay attacks and reduce the delay time of the entire authentication process.